ANALISIS KELAYAKAN AGROINDUSTRI VIRGIN COCONUT OIL(STUDI KASUS KELOMPOK TANI ANUGRAH KELURAHAN TANDURUSA KECAMATAN AERTEMBAGA KOTA BITUNG) - Sakila ., Rahman; Vicky V.J. Palenewen; Femi H. Elly (AGRI-SOSIOEKONOMI, 2016)
This study aims to analyze how much profit out of the business of agro-industry Virgin Coconut Oil and analyzing the feasibility of agroindustrial Virgin Coconut Oil of Grace Farmers Group in Tandurusa Village Aertembaga Sub=District, District of Bitung. This research method is a method of Agro-industry survey on business Tandurusa Grace Farmer Group. Data were collected through interviews using a questionnaire technique. Methods of sample collection is done use purposive sampling) are members of farmer groups Grace. Analyzed using profits to the equation TC = TFC + TVC, TR = Q. P, Î  = TR - TC. Then proceed to calculate the value of R / C which is the ratio between the total revenue with total costs incurred during the production process, wherein if R / C> 1 = worthy, R / C = 1 = breakeven, R / C <1 = not feasible. To find out if this Virgin Coconut Oil Agroindustri no profit or loss by the use of analysis Break Even Point (BEP). Result analysis and discussion shows that the total variable cost is Rp. 81.96 million, / year and total fixed costs are Rp.8.295.000, - / year, while total revenue was Rp. 249 600 000, - and BEP production was 61.75 liters and the BEP price is Rp.12.343.750 / year and Rp. 1,028.645, - / month and Rp. 85.720, - / 2day. Total profit / year is Rp. 159 345 000, - / year. With the value of R / C ratio is 3, so that it can be concluded that the Virgin Coconut Oil Agroindustri Poktan Grace Village Tandurusa experiencing gains and financially feasible to be developed because it exceeds the BEP and also R / C Ratio of her that is> 1. Fluctuations in the price and availability of raw materials greatly influence Virgin Coconut Oil production. Venture capital also influences the production of Virgin Coconut Oil. Agribusiness Virgin Coconut Oil provides an opportunity to increase income of farmers' income and employment opportunities and improve the State Foreign Exchange.